2011
DOI: 10.5761/atcs.cr.09.01501
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac Metastasis of Esophageal Squamous Cell Carcinoma: Report of a Case

Abstract: We report a case of a 48-year-old man with a history of violent coughing fits and general fatigue underwent urgent surgery for cardiac tamponade, and who was later diagnosed with metastatic intracardiac squamous cell carcinoma of the esophagus. After admittance to Munakata Suikokai General Hospital, Fukuoka, Japan, echocardiography showed extensive pleural and pericardial effusion and a mass, 4 by 2 cm, with a solid echo pattern in the right ventricular cavity. The working diagnosis was primary malignant cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In all, 12 cases were solitary cardiac metastases. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Most of the cardiac metastasis are detected on autopsy studies. These studies reported the incidence of cardiac metastasis was 2.3%-18.3% of cancer patients and 0.2%-6.5% of unselected autopsy series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 12 cases were solitary cardiac metastases. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Most of the cardiac metastasis are detected on autopsy studies. These studies reported the incidence of cardiac metastasis was 2.3%-18.3% of cancer patients and 0.2%-6.5% of unselected autopsy series.…”
Section: Discussionmentioning
confidence: 99%
“…According to the past 15 reports of cardiac metastasis from esophageal cancer, the median time from the detection of primary tumor to the onset of cardiac metastasis was 8.9 months. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The differential diagnosis of cardiac mass is difficult. In case of a cardiac tumor, metastasis is more frequent than a primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Generally patients symptomatic for intracardiac metastases die within a few weeks; sometimes resection of cardiac metastases can be attempted, but median survival is 4 weeks (3, 12, 13). Our patient survived 1 year between diagnosis and death and the cardiac lesion remained the only one.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac involvement is generally a sign of disseminated disease. Surgical resection of cardiac metastases is recommended only for single intracardiac lesions; the treatments of choice are chemotherapy and/or radiotherapy, for palliative purposes and relief of symptoms (3).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac tamponade and pericardial effusions have previously been reported in association with various cancers including oesophageal cancers 1. There are many mechanisms, including direct invasion, metastasis and post radiotherapy 2. Rarely oesophageal pericardial fistulas (OPF) have been reported as the culprits 3.…”
Section: Introductionmentioning
confidence: 99%